Network characterization using constraint-based definitions of capacity, utilization, and efficiency. - Yegenoglu, Ferit (IEEE Communications magazine)
Capacity planning in an operational network requires continuous monitoring of network resources so that corrective actions can be taken in response to changes in traffic patterns, performance requirements, and network technology. In this article we characterize network resources in terms of capacity, utilization, and efficiency, and define these metrics as functions of the sets of constraints under which the network is operating. These constraints may include service level agreement objectives, routing policy constraints, and failure survivability requirements. Constraint-based network characterization allows a network operator to quantify the inherent capacity of a network and determine the impact of changes in operating conditions on realizable capacity. It also helps assess how well a given network design matches the set of constraints under which it is operating, how much traffic growth the network can support, and what actions need to be taken to accommodate traffic growth.